The Marshall Plan as a catalyst for European integration : a neo-functionalist edifice on a neo-realist ground - Polat, Hilal (My University, 2020)
II. Dünya Savaşı sonrasında, Avrupa kıtlık ve yüksek seviyedeki işsizlik ile birlikte, çatışmaların getirdiği yıkımdan muzdaripti. Ancak ABD, savaş esnasında sağlanan ekonomik büyüme sayesinde bir süper güç olarak ortaya çıktı. Batı Avrupa, başka bir süper güç olan Sovyetler Birliği tehdidi altına girmek üzereydi. Böylece, Avrupa Kalkınma ERP) olarak da bilinen Marshall Planı, bir canlanma ve işbirliği aracı olarak ortaya çıktı. Bu tez, Marshall Planı’nın II. Dünya Savaşı sonrası Avrupa entegrasyon sürecini Avrupa Ekonomik Topluluğu'nun oluşturulması sürecine kadar nasıl etkilediğini analiz etmeyi amaçlamaktadır. Savaş sonrası transatlantik ilişkiler ve koordinasyona odaklanan tez çalışması, savaş sonrası Amerikan dış politikasının Avrupa devletlerinde, özellikle Almanya-Fransa ilişkileri bağlamında, Alman sorununa odaklanarak nasıl etkilediğini açıklamaktadır. Bu çalışma, iki farklı teorinin varsayımları ile Marshall Planı’nın Avrupa bütünleşmesinin ilk zamanlarındaki etkisini incelemektedir. Bu bağlamda, bütünleşme sürecinin başlangıcı neo-realist bir mercekle incelenirken, yeni-işlevselcilik ise sürecin devamını yorumlamak için bir araç olarak uygulanmıştır. Bu tez çalışması, Soğuk Savaş’ın başlangıcında gelişen olaylar da dahil olmak üzere ABD-Avrupa ilişkilerinin incelenmesine teorik bir katkı sunmaktadır.

In the aftermath of World War II, Europe was suffering from the devastation brought by conflict, together with food shortages and high unemployment. However, the US emerged as a superpower with economic growth that was achieved during the war. Western Europe was about to fall under the threat of another superpower, the Soviet Union. Hence, the Marshall Plan, also known as the European Recovery Program (ERP), was created as a means of revival and cooperation. The thesis aims to analyze how the Marshall Plan affected the post-World War II European integration process until the creation of the European Economic Community (EEC). With a focus on post-war transatlantic relations and coordination, the thesis elucidates how post-war American foreign policy influenced the relations in the European states, especially between Germany and France, focusing on the German problem at that time. The thesis examines the effect of the Marshall Plan on the early European integration through the assumptions of two different theories. In this vein, the beginning of the integration process is examined through a neo-realist lens, while neo-functionalism is applied as a means to provide an interpretation of its progression. The thesis offers a theoretical contribution to the study of US-European relations, including the events revolving around at the start of the Cold War.
Keywords: ABD; Avrupa Birliği; Avrupa Bütünleşmesi; European Union; Marshall plan; Marshall planı; Neo-Functionalism; Neo-Realism; Neo-Realizm European Integration; Political science; Siyasal bilim; the US; Transatlantic Relations; Transatlantik İlişkiler; Yeni-İşlevselcilik